A new table of Balmer line shapes for the diagnostic of magnetic fusion plasmas. (January 2017) - Rosato, J.; Marandet, Y.; Stamm, R.
Abstract: A new table of Stark–Zeeman line shapes is provided for plasma diagnostics in the framework of magnetic fusion research. Spectral profiles of D α, D β, D γ, D δ, and D ε have been calculated using computer simulations in conditions relevant to tokamak edge and divertor plasmas. After a brief presentation of the calculation method, we propose an interpolation formula and we give a routine for diagnostic applications. Analyses of experimental and synthetic spectra are performed as an illustration. Abstract : Highlights: A new table of Stark–Zeeman line shapes is provided for plasma diagnostics. The calculations were performed using a computer simulation technique, which serves as a reference in the elaboration of Stark broadening models. Analyses of experimental and synthetic spectra in tokamak divertor plasma conditions are performed as an illustration.